Endoscopic Orbital Clearance/Debridement: A Potential Substitute for Orbital Exenteration in Rhino-orbital Mucormycosis - Ahmed Hassan Sweed; Ahmed Mohammad Anany; Atef Hussein; Waleed Nada; Mohamed Eesa; Ismail Elnashar; Mohamed Mobashir; Enas Moustafa Ibrahim; Mohammed Elsayed Elmaghawry (International Archives of Otorhinolaryngology)
Introduction Mucormycosis is an aggressive, lethal fungal infection affecting the nasal and paranasal territory in immunocompromised patients. Orbital involvement is not uncommon and may require orbital exenteration.